Genre-plot typology of interior decorative painting in Chinese painting of the beginning of the 21st century - Chоng Dingye (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article is devoted to Chinese decorative painting of the beginning of the 21st century. The purpose of the article is the genre-plot typology of the interior decorative painting in Chinese painting of the beginning of the 21st century. It is indicated that the actualization of the problem of the development of interior decorative painting was due to the dynamic urbanization of China, the improvement of the living conditions of ordinary citizens of the country since the beginning of the 21st century. The author examines the state of Chinese and foreign scientific discourse on the mentioned problem. The research methodology is based on the use of both general scientific methods of analysis and special art-scientific ones, namely: the method of morphological typology and the method of analyzing symbolic artistic forms. The given genre-plot typology of the interior decorative painting in Chinese painting of the beginning of the 21st century showed that the problematization of the genre typology of this art branch should take into account both the genre level of the canonical system of Chinese painting and the genre thesaurus of the non-canonical system of decorative painting. These are the so-called “hybrid genres”, which are the result of the use of a fairly diverse global genre thesaurus. The article proves that the plot typology of modern Chinese interior decorative painting is based on the deep mechanisms of symbolization in the narrative structures of pictorial art forms, which are decisive both for the national artistic and cultural heritage and for modern Chinese decorative painting. The basis of such a typology is the system of “benevolent” ornament, which has been developed in China for thousands of years. In the course of the analysis, several types of plots, which are currently actively produced by artists for the design of private and public interior spaces, were identified, namely: mythological and religious plots, historical plots and genre plots, which also include the so-called “landscape narrative”. The research opens the perspective of studying the festive decorative painting and its genre-plot typology, as well as the compositional and color solution of the decorative painting in Chinese painting of the beginning of the 21st century.